Usability evaluation of the state junior high school 40 palembang website using the system usability scale (SUS) - Muhammad Yunus Syafaruddin; Ari Muzakir Muzakir; Megawaty (Journal of Information System and Artificial Intelligence, 2025)
The increasing reliance on digital platforms in education highlights the importance of website usability for supporting academic and administrative activities. This study evaluates the usability of the State Junior High School 40 Palembang website using the System Usability Scale (SUS), a widely adopted and reliable method for measuring user experience. Data were collected from 50 respondents representing students, teachers, and administrative staff through observations, documentation, and an online SUS questionnaire. The overall SUS score achieved was 75.6, which places the website in the Good usability category. Further analysis revealed differences among user groups: administrative staff rated the system as Excellent (82.5), teachers as Good but close to Excellent (78.0), and students as Good but with the lowest score (72.5). These variations indicate that user familiarity, task type, and device context strongly influence usability perception. Benchmark comparisons confirmed that while the website surpasses the global average threshold, improvements are required to elevate it to the Excellent level consistently across all groups. Key areas for enhancement include navigation consistency, user guidance, and mobile responsiveness. Addressing these aspects will ensure broader user satisfaction, higher efficiency, and alignment with best practices in educational website usability.